Enhancing secondary metabolite production in plants: Exploring traditional and modern strategies - Nidhi Selwal; Farida Rahayu; Anik Herwati; Evy Latifah; Supriyono; Cece Suhara; Ida Bagus Kade Suastika; Weda Makarti Mahayu; Atif Khurshid Wani (Journal of Agriculture and Food Research, 2023)
The biosynthesis of secondary metabolites (SMs) in plants occurs in various forms and amounts, and their use in modern medicine is widespread. Half of the human necessities are derived from plant-based commodities, including fuel, cosmetics, pharmaceuticals, building materials, and food essentials. Many medicinal plant species are utilized for their therapeutic properties and their SMs content, but the amount of naturally occurring SMs in plants are limited. Therefore, various conventional and novel strategies are employed to enhance the production of bioactive components from plants. Traditional methods are cost-effective, easy, and faster, but produce fewer metabolites, while modern techniques such as metabolic pathways engineering, genome editing, metabolic transformation, biotechnology-based substitutions, and synthetic biology are more expensive but offer valuable tools for augmenting SMs content. Optimizing culture media and signalling pathways involved in SMs production presents an exciting opportunity to increase the quantity of bioactive compounds naturally present. This review summarizes the different cultivation methods used to enhance the class and quantity of metabolites produced and highlights the benefits of strategies for boosting SMs and synthesizing metabolites using various techniques.